(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
This current study attempts to provide an investigation of service industry growth in the most troublesome areas of Russia. The idea that the growth of industry service in several areas would assist in stabilizing socially dire segments of the economy, the labor market, is scrutinized. Today, the socio-economic issues influencing the job world are the outcome of inadequate management regulation in this arena. The demolition of production bonds, the large production plants’ privatization, and their poor management resulted in a sharp fall in the need for labor and also a rise in unemployment. The local authorities are still not able to resolve the issue of unemployment in some areas of Russia. What’s more, several social groups’ condition is getting more complex on a yearly basis. That may entail detrimental outcomes, particularly in the Russian areas. Considering boosting the overall condition of the labor market, it appears that there is a necessity to alleviate the employers’ demands for job-seeker people.